Hybrid-Actuated Finger Prosthesis with Tactile Sensing. (14th October 2013) - Low, Cheng Yee; Kasim, M. Amlie A.; Koch, Torben; Dumitrescu, Roman; Yussof, Hanafiah; Jaafar, Roseleena; Jaffar, Ahmed; Aqilah, Ahsana; Ng, Kok Mun
Finger prostheses are devices developed to emulate the functionality of natural human fingers. On top of their aesthetic appearance in terms of shape, size and colour, such biomimetic devices require a high level of dexterity. They must be capable of gripping an object, and even manipulating it in the hand. This paper presents a biomimetic robotic finger actuated by a hybrid mechanism and integrated with a tactile sensor. The hybrid actuation mechanism comprises a DC micromotor and a Shape Memory Alloy (SMA) wire. A customized test rig has been developed to measure the force and stroke produced by the SMA wire. In parallel with the actuator development, experimental investigations have been conducted on Quantum Tunnelling Composite (QTC) and Pressure Conductive Rubber (PCR) towards the development of a tactile sensor for the finger. The viability of using these materials for tactile sensing has been determined. Such a hybrid actuation approach aided with tactile sensing capability enables a finger design as an integral part of a prosthetic hand for applications up to the transradial amputation level.